The perceived global impact of the COVID‐19 pandemic on doctors' medical and surgical training: An international survey. Issue 8 (24th May 2021) - Laloo, Ryan; Santhosh Karri, Rama; Wanigasooriya, Kasun; Beedham, William; Darr, Adnan; Layton, Georgia R; Logan, Peter; Tan, Yanyu; Mittapalli, Devender; Patel, Tapan; Mishra, Vivaswan Dutt; Odeh, Osama Faleh; et al.
Abstract: Introduction: The COVID‐19 pandemic has resulted in a significant burden on healthcare systems causing disruption to the medical and surgical training of doctors globally. Aims and Objectives: This is the first international survey assessing the perceived impact of the COVID‐19 pandemic on the training of doctors of all grades and specialties. Methods: An online global survey was disseminated using Survey Monkey ® between 4th August 2020 and 17th November 2020. A global network of collaborators facilitated participant recruitment. Data were collated anonymously with informed consent and analysed using univariate and adjusted multivariable analyses. Results: Seven hundred and forty‐three doctors of median age 27 (IQR: 25‐30) were included with the majority (56.8%, n = 422) being male. Two‐thirds of doctors were in a training post (66.5%, n = 494), 52.9% (n = 393) in a surgical specialty and 53.0% (n = 394) in low‐ and middle‐income countries. Sixty‐nine point two percent (n = 514) reported an overall perceived negative impact of the COVID‐19 pandemic on their training. A significant decline was noted amongst non‐virtual teaching methods such as face‐to‐face lectures, tutorials, ward‐based teaching, theatre sessions, conferences, simulation sessions and morbidity and mortality meetings ( P  ≤ .05). Low or middle‐income country doctors' training was associated with perceived inadequate supervision while performing invasive procedures under general, local or regional anaesthetic. ( P  ≤ .05). Conclusion: In addition to the detrimental impact of the COVID‐19 pandemic on healthcare infrastructure, this international survey reports a widespread perceived overall negative impact on medical and surgical doctors' training globally. Ongoing adaptation and innovation will be required to enhance the approach to doctors' training and learning in order to ultimately improve patient care.